In vivo assessment of GABAergic inhibition and glutamate facilitation in treatment-resistant schizophrenia: a TMS study integrating clinical, cognitive, and neurophysiological evaluations - Annarita Barone; Gianmaria Senerchia; Giuseppe De Simone; Marco Manzo; Mariateresa Ciccarelli; Stefano Tozza; Valentina Virginia Iuzzolino; Myriam Spisto; Raffaele Dubbioso; Felice Iasevoli; Rosa Iodice; Andrea de Bartolomeis (Schizophrenia)
Abstract Treatment-resistant schizophrenia (TRS) affects approximately one-third of individuals with schizophrenia, posing significant challenges for clinical management. Clozapine treatment is often delayed, underscoring the urgent need for an early potential signature of TRS. To date, specific alterations in cortical excitability and plasticity underlying TRS remain unexplored. We evaluated cortical excitability and plasticity in 30 patients with schizophrenia (15 TRS, 15 non-TRS) and 21 controls using transcranial magnetic stimulation (TMS). Measures included motor thresholds and protocols probing GABAergic inhibition and glutamatergic facilitatory activity, the excitation index (EI) in the primary motor cortex (M1), and long-term potentiation (LTP)-like plasticity using intermittent theta burst stimulation (iTBS). Clinical severity and cognitive performance were evaluated using the Positive and Negative Syndrome Scale (PANSS) and the Brief Assessment of Cognition in Schizophrenia (BACS). TRS patients exhibited significantly higher active motor thresholds (p = 0.015) and impaired short-interval intracortical inhibition (SICI) (p = 0.001) vs healthy controls, reflecting GABAergic dysfunction. EI was elevated in TRS vs non-TRS patients (p = 0.034) and controls (p = 0.002), indicating pronounced cortical hyperexcitability. Both TRS (p = 0.008) and non-TRS patients (p = 0.033) showed reduced plasticity following iTBS compared to controls, with no TRS vs non-TRS difference. SICI deficits significantly correlated with negative (r = 0.524, p adj = 0.03) and autistic (r = 0.517, p adj = 0.03) symptom severity as assessed by the PANSS negative score and Positive and Negative Syndrome Scale Autism Severity Score (PAUSS). Our findings point to a neurophysiological continuum in schizophrenia, with TRS patients demonstrating the most pronounced cortical hyperexcitability and impaired plasticity, and non-TRS patients showing intermediate deficits.